National trends in endovascular thrombectomy and decompressive craniectomy for acute ischemic stroke: A study using National Inpatient Sample data from 2006 to 2016. (July 2022) - Gravbrot, Nicholas; McDougall, Riley; Aguilar-Salinas, Pedro; Avila, Mauricio J.; Burket, Aaron R.; Dumont, Travis M.
Highlights: Evidence for thrombectomy benefit with novel devices was first demonstrated in 2015. Here, we report US trends for thrombectomy and craniectomy from 2006 to 2016. Thrombectomy increased steadily; craniectomy first increased but declined in 2016. Abstract: Background: Ischemic stroke is a frequently encountered neurologic process with wide-spanning impact. A dreaded complication is "malignant" cerebral edema, necessitating decompression to reduce herniation risk. Following the publication of several landmark trials in 2015, endovascular thrombectomy (EVT) with novel clot-removal devices has emerged as an effective treatment for proximal large vessel disease. Herein, we examine recent national trends in EVT and decompressive craniectomy (DC) rates for acute stroke. Methods: National Inpatient Sample data were abstracted from 2006 to 2016. Primary outcomes were EVT and DC rates, compared using Cochrane-Armitage test of trend. Chi-square test was also used to compare data from 2015 to 2016. Secondary outcomes included inpatient mortality and home discharge rates. Results: EVT rates steadily increased from 2006 to 2016, with most change occurring from 2014 to 2016 (1.36% in 2014, 2.29% in 2016). DC rates similarly increased from 2006 to 2015, though a sharp decline was observed in 2016 (0.42% in 2015, 0.22% in 2016). Test of trend from 2006 to 2016 for both variables was found to be statistically significant (p = 0.001); DC rate change from 2015 to 2016 was also statistically significant (p < 0.01). Mortality rate and home discharge rate steadily improved over the study period. Conclusions: Recent innovation in stroke treatment has led to increased EVTs. While DC rate initially followed this same trend, a significant decline was noted in 2016, around the time that wider adoption of novel EVT technologies were instituted in clinical practice.